Short-term debt and incentives for risk-taking - Della Seta, Marco; Morellec, Erwan; Zucchi, Francesca (Journal of Financial Economics, 2020)
We challenge the view that short-term debt curbs moral hazard and demonstrate that, in a world with financing frictions and fair debt pricing, short-term debt generates incentives for risk-taking. To do so, we develop a model in which firms are financed with equity and short-term debt and cannot freely optimize their default decision because of financing frictions. We show that when firms are close to distress, the dynamic interaction of operating and rollover losses fuels default risk. In such instances, shareholders find it optimal to increase asset risk to improve interim debt repricing and prevent inefficient liquidation. These risk-taking incentives do not arise when debt maturity is sufficiently long.